Innovation in Smart Maintenance: An IoT-Based Strategy to Improve Packaging Machine Availability in a SME - Delzo-Fajardo, Susy; Grandez-Ulloa, Rosa; Saenz-Moron, Martin; Straujuma, Anita (LACCEI, 2025)
In the context of the highly competitive food sector in emerging regions, enhancing operational efficiency is essential for business sustainability. This study presents an innovative model aimed at improving the availability of oatmeal packaging machines in a Peruvian company by integrating emerging technologies with industrial engineering methodologies. The proposed approach combines the pillars of Autonomous and Planned Maintenance from the Total Productive Maintenance (TPM) framework with inventory management based on the SCOR model, incorporating a smart maintenance strategy through IoT sensors connected to a cloud-based platform. This technological solution enables real-time monitoring of machine conditions and supports data-driven operational decision-making. The implementation led to an 8.71% increase in machine availability (from 86.64% to 95.36%), a 68.68% reduction in unplanned downtimes, and a 78.78% decrease in stoppage time due to material and spare parts stockouts. Beyond the technical outcomes, this model represents a case of intrapreneurship within the operations team, demonstrating how internal innovation can transform traditional maintenance practices and contribute to the evolution of the business model. The solution is scalable and adaptable to other companies in the Latin American food industry, strengthening industrial competitiveness and promoting sustainable innovation in emerging markets.